Preparation method of high-stain-resistant decorative paper
Patent Information
- Application Number
- CN202611376702.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]现有的技术一般是在印刷装饰原纸上涂覆一层水性丙烯酸树脂、水性聚氨酯、聚氨酯丙烯酸酯或者有机硅改性的涂料作为保护层,在普通的热塑性水性树脂涂层中交联度较低,受到反复擦拭、湿热或者磨耗等会易发生发黏、失光以及耐污性能下降等问题,一般的紫外光固化的涂层可以缩短固化的时间但是单一波段的紫外光容易受到涂层厚度、颜料遮蔽、水分残留、氧阻聚的影响,如果表面固化速度快于内部固化速度,则会出现表层已经固化而靠近纸基的一侧还存在固化不足的现象,会影响涂层的附着、耐磨性和收卷稳定问题,如果仅仅通过提高总的辐照剂量来补偿,又可能会造成纸张受热过多导致图案色差大、生产能耗高
1、本申请在水分散型聚羟基氨基甲酸酯的制备过程中,以多官能环状碳酸酯与高分子聚醚胺进行开环加成,并引入含氨基超支化聚硅氧烷,全程不加入二异氰酸酯、多异氰酸酯或封闭型异氰酸酯。与常规水性聚氨酯依赖异氰酸酯预聚、亲水扩链和胺扩链的路线相比,可从原料及制备路径上减少未反应异氰酸酯单体进入涂料和成品装饰纸的可能性,降低生产人员接触以及装饰纸在室内长期使用时发生相关残留释放的风险。同时,所得成膜组分能够直接水分散,抗污涂料以水作为主要分散介质,并配合大分子光引发剂和可聚合紫外吸收剂,减少小分子光固化助剂固化后迁移、析出或形成气味的可能性,使材料安全性、施工环境适应性和室内装饰应用要求得到兼顾。
Smart Images

Figure CN122980260A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of polyurethane coating and decorative paper processing technology, specifically relating to a method for preparing highly stain-resistant decorative paper using non-isocyanate type water-dispersible polyhydroxycarbamate and multi-band ultraviolet curing process. Background Technology
[0002] Decorative paper is generally made from titanium dioxide decorative base paper, printed with water-based inks to create various decorative patterns such as wood grain, stone grain, or others. It is then applied to furniture boards, flooring, wall panels, and interior finishing materials using methods such as impregnation, lamination, or pressing. During production and transportation, decorative paper comes into contact with various contaminants such as soy sauce, coffee, cooking oil, oil-based marker residue, and everyday cleaning agents. Once these contaminants enter the pores of the paper surface or adhere to the printed layer, they are difficult to remove using ordinary wiping methods and may cause problems such as discoloration of the pattern, localized loss of gloss, and expansion of stains. Improving the surface stain resistance, ease of cleaning, and abrasion resistance of decorative paper without affecting its thickness (not obscuring the printed pattern) and its subsequent lamination performance is one of the problems that needs to be solved in the decorative paper processing industry.
[0003] Existing technologies typically involve coating the printing and decorative base paper with a layer of water-based acrylic resin, water-based polyurethane, polyurethane acrylate, or silicone-modified coating as a protective layer. In ordinary thermoplastic water-based resin coatings, the degree of cross-linking is low, and repeated wiping, damp heat, or abrasion can easily lead to problems such as stickiness, loss of gloss, and decreased stain resistance. While UV-cured coatings can shorten curing time, single-band UV light is easily affected by coating thickness, pigment obscuration, moisture residue, and oxygen inhibition. If the surface curing speed is faster than the internal curing speed, the surface layer may be cured while the side closer to the paper base remains undercured, affecting coating adhesion, abrasion resistance, and winding stability. If compensation is only achieved by increasing the total irradiation dose, it may cause excessive heating of the paper, resulting in large color differences in the pattern and high production energy consumption.
[0004] Conventional waterborne polyurethane or waterborne polyurethane acrylate typically requires the preparation of prepolymers from diisocyanates and polymeric polyols, followed by hydrophilic chain extension, neutralization, and water dispersion. This route places high demands on the water content of the raw materials, the ratio of isocyanate groups to hydroxyl groups, and the chain extension conditions. Inadequate reaction control can lead to the presence of unreacted diisocyanate monomers or related low-molecular-weight substances in the resin. Decorative paper, primarily used in furniture, wall panels, and interior finishes, covers a large area and has a long service life. Therefore, in addition to considering its stain resistance, it is crucial to control the free isocyanates, small-molecule photoinitiators, and residual additives in the coating. Furthermore, simply adding silicone additives or inorganic nanoparticles to the coating to achieve initial improvements in surface smoothness and stain resistance may still result in uneven dispersion, migration, precipitation, or diminished effectiveness after abrasion.
[0005] For example, Chinese invention patent application CN115109510A discloses a stain-resistant UV coating, its preparation method, and its application. The disclosed coating uses an organosilicon-modified polyurethane acrylate oligomer UV-curing emulsion, a fluorosilicone-modified polyurethane emulsion, and polyether-modified polydimethylsiloxane containing acrylate functional groups as anti-graffiti additives to improve the stain resistance and durability of the water-based UV coating. This technology also relates to water-based polyurethane stain-resistant coatings and UV curing techniques, but its intended applications are automotive interiors and instrument panels. For products such as plastic casings for electronic products, the production process involves spraying, leveling, and a single UV curing step. However, this process does not disclose the preparation of non-isocyanate polyhydroxycarbamate using polyfunctional cyclic carbonates and high-molecular-weight polyetheramines, nor does it involve adding amino-containing hyperbranched polysiloxanes during the preparation of the main resin. Furthermore, it does not cover the process of sequentially performing long-wave internal pre-curing and short-wave surface curing on the printing and decorative paper. Therefore, it does not focus on solving the problems of low coating weight continuous roll coating of decorative paper, internal curing of the paper base, protection of printed patterns, and control of isocyanate residue.
[0006] Therefore, there is a need to provide a method for preparing highly stain-resistant decorative paper for printing decorative base paper, which enables the film-forming components to be stably dispersed in water without the use of isocyanate compounds. Furthermore, the method utilizes a combination of amino-hyperbranched polysiloxanes, multi-band photocurable components, polymerizable light-stabilizing components, and inorganic functional components to improve the coating's easy-to-clean, abrasion-resistant, and light-stable properties. In addition, the coating amount, pre-drying conditions, and curing sequence of different wavelengths of ultraviolet light should be rationally set according to the liquid absorption of different paper substrates and the actual situation of continuous production to ensure that the coating achieves sufficient curing on both the surface and the side closest to the paper substrate, and to reduce the safety impact of coating residues on indoor use. Summary of the Invention
[0007] To address the aforementioned deficiencies, this application provides the following technical solution: a method for preparing highly stain-resistant decorative paper, comprising the following steps: S1: A water-dispersible polyhydroxycarbamate is prepared by ring-opening addition of a multifunctional cyclic carbonate, a high molecular weight polyetheramine and an amino-containing hyperbranched polysiloxane and then water-dispersed. No isocyanate compound is added during the reaction. S2: Mix the water-dispersible polyhydroxycarbamate with a multi-band photocurable component, a polymerizable light-stabilizing component and an inorganic functional component to prepare an anti-fouling coating; S3: Roll-coat the anti-fouling coating onto the surface of the printed decorative base paper, with a coating amount of 5g / m². 2 ~20g / m 2 Pre-dry at 45℃~65℃ for 1min~5min; S4: Internal pre-curing is performed using 395nm~405nm ultraviolet light, followed by surface curing using 365nm~385nm ultraviolet light to obtain highly stain-resistant decorative paper.
[0008] Further, in step S2, based on 100 parts by weight of the polyhydroxycarbamate solid in the water-dispersible polyhydroxycarbamate, the antifouling coating comprises 100 parts of water-dispersible polyhydroxycarbamate, 15-30 parts of water-dispersible multifunctional UV crosslinking agent, 0.5-1.5 parts of long-wavelength macromolecular photoinitiator, 0.5-1.5 parts of short-wavelength macromolecular photoinitiator, 0.5-1.5 parts of polymerizable UV absorber, 1-3 parts of nano-silica, 0.5-1.5 parts of nano-zinc oxide, 0.2-0.8 parts of sodium polyacrylate, 0.05-0.40 parts of 2,4,7,9-tetramethyl-5-decyn-4,7-diol, and 15-40 parts of water.
[0009] Further, in step S1, the water-dispersible polyhydroxycarbamate is prepared according to the following steps: S1.1: The polyfunctional cyclic carbonate, the high molecular weight polyetheramine, and the amino-containing hyperbranched polysiloxane are mixed in a mass ratio of 100:18 to 45:3 to 12. The mixture is then reacted at 70°C to 95°C for 2 to 5 hours. S1.2: Add the remaining high molecular weight polyetheramine and amino-containing hyperbranched polysiloxane, and react at 60℃~85℃ for 1h~4h, wherein the molar ratio of cyclic carbonate groups to amino active hydrogen is 1.02:1~1.15:1; S1.3: Add 0.5wt% to 4wt% of propylene carbonate relative to the polyfunctional cyclic carbonate, react at 55℃ to 75℃ for 0.5h to 2h, then add water and disperse at 1000r / min to 3000r / min for 10min to 40min to obtain the water-dispersible polyhydroxycarbamate.
[0010] Further, the multifunctional cyclic carbonate is carbonated epoxidized soybean oil or carbonated epoxidized linseed oil, and is prepared according to the following steps: commercially available epoxidized soybean oil or commercially available epoxidized linseed oil is placed in a reaction vessel, 0.3wt% to 1.5wt% of a quaternary ammonium salt catalyst relative to its mass is added, carbon dioxide is introduced to a pressure of 1.0MPa to 3.5MPa, and the reaction is carried out at 90℃ to 130℃ for 6h to 16h; the quaternary ammonium salt catalyst is one or more of tetrabutylammonium bromide, tetrabutylammonium iodide, or tetraethylammonium bromide.
[0011] Further, the amino-containing hyperbranched polysiloxane is prepared according to the following steps: 20-50 parts by weight of 3-aminopropyltriethoxysilane, 40-70 parts by weight of methyltriethoxysilane, and 5-20 parts by weight of trimethylethoxysilane are mixed; 20-60 parts by weight of water, 50-150 parts by weight of ethanol, and 5-20 parts by weight of 1% hydrochloric acid are mixed and added dropwise to the silane mixture at 20℃-35℃ for 30-90 minutes; after the addition is completed, a hydrolysis-condensation reaction is carried out at 50℃-75℃ for 3-8 hours, and ethanol and water are removed under conditions of 45℃-65℃ and a vacuum of -0.06MPa--0.09MPa to obtain the amino-containing hyperbranched polysiloxane.
[0012] Further, the polymeric polyetheramine is one or more of polyoxypropylene diamine D-230, polyoxypropylene diamine D-400, polyoxypropylene diamine D-2000, or polyoxypropylene triamine T-403; the water-dispersible multifunctional UV crosslinking agent is one or more of polyethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate, or ethoxylated bisphenol A dimethacrylate; the nano silica is one or more of fumed hydrophilic nano silica, silica sol nano silica, or γ-methacryloyloxypropyltrimethoxysilane modified nano silica; the nano zinc oxide is unmodified by organic surface treatment and has an average primary particle size of 20 nm to 50 nm.
[0013] Further, the long-wavelength macromolecular photoinitiator is the polymeric TPO-L photoinitiator Omnipol TP, or is composed of the polymeric thioxanthone photoinitiator GENOPOL TX-2 and the polymeric amine synergist GENOPOL AB-2 in a mass ratio of 1:0.5 to 1.5; the short-wavelength macromolecular photoinitiator is the polymeric aminoalkyl benzophenone photoinitiator Omnipol 910, or is composed of the bifunctional benzophenone photoinitiator Omnipol BP and the polymeric amine synergist Omnipol ASA in a mass ratio of 1:0.5 to 1.5.
[0014] Further, the polymerizable ultraviolet absorber is one or more of 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl methacrylate, 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone or 4-methacryloyloxy-2-hydroxybenzophenone.
[0015] Further, in step S3, the printed decorative base paper is processed with a basis weight of 65 g / m³. 2 ~100g / m 2 The water-based decorative ink is obtained by gravure printing on the surface of titanium dioxide decorative base paper and drying it. The dry coating weight of the water-based decorative ink is 0.8 g / m². 2 ~3.0g / m 2 The drying temperature is 70℃~100℃, and the drying time is 30s~120s. The anti-fouling coating is applied by an anilox roller in the forward direction, with a roller speed of 12m / min~35m / min and an inter-roller pressure of 0.20MPa~0.60MPa.
[0016] Furthermore, in step S4, when internal pre-curing is performed using 395nm–405nm ultraviolet light, the irradiation intensity is 0.5W / cm². 2 ~1.5W / cm 2 The irradiation dose was 200 mJ / cm. 2 ~600mJ / cm 2 After internal pre-curing, a 1-20 second interval is maintained before surface curing using 365nm-385nm ultraviolet light at an irradiation intensity of 0.8W / cm². 2 ~2.0W / cm 2 The irradiation dose was 300 mJ / cm. 2 ~900mJ / cm 2 After surface curing, cool at 20℃~35℃ for 1min~5min. The technical solution of this application has the following beneficial effects: 1. In the preparation of water-dispersible polyhydroxycarbamate, this application involves ring-opening addition of polyfunctional cyclic carbonates with high-molecular-weight polyetheramines, and the introduction of amino-containing hyperbranched polysiloxanes, without the addition of diisocyanates, polyisocyanates, or blocked isocyanates throughout the process. Compared with conventional waterborne polyurethane routes that rely on isocyanate prepolymerization, hydrophilic chain extension, and amine chain extension, this approach reduces the possibility of unreacted isocyanate monomers entering coatings and finished decorative paper from the perspectives of raw materials and preparation pathways, thereby reducing the risk of contact with production personnel and the release of related residues during long-term indoor use of decorative paper. Simultaneously, the resulting film-forming components can be directly dispersed in water, with water serving as the primary dispersion medium in the anti-fouling coating. Furthermore, the combination of macromolecular photoinitiators and polymerizable UV absorbers reduces the possibility of migration, precipitation, or odor formation of small-molecule photocuring additives after curing, thus balancing material safety, adaptability to the construction environment, and the requirements of indoor decoration applications.
[0017] 2. This application does not rely solely on nano-silica or nano-zinc oxide to impart stain resistance. Instead, it uses water-dispersible polyhydroxycarbamate as a continuous film-forming component, introducing amino-containing hyperbranched polysiloxane during the main resin preparation stage. This, combined with a water-dispersible multifunctional UV crosslinking agent, nano-silica, unmodified nano-zinc oxide, sodium polyacrylate, and acetylenol wetting agent, constitutes a comprehensive anti-fouling system. Sodium polyacrylate and acetylenol wetting agent facilitate uniform dispersion of inorganic components in the water-based coating and continuous spreading of the coating on the printing paper, preventing particle agglomeration, pinholes, or uneven local coating that weakens the decorative effect. The amino-containing hyperbranched polysiloxane cures together with the main film-forming component, which helps maintain easy-to-clean properties under repeated wiping and abrasion conditions. Therefore, the resulting coating can simultaneously resist different types of contaminants such as soy sauce, coffee, cooking oil, and oil-based markers, not only reducing initial contamination residue but also minimizing the rapid decline in stain resistance due to surface additive migration or wear.
[0018] 3. This application employs a sequential process of first performing internal pre-curing with 395nm–405nm ultraviolet light, followed by surface curing with 365nm–385nm ultraviolet light, with specific limits on the irradiation intensity, irradiation dose, and curing interval for each stage. The longer wavelength ultraviolet light acts first on the pre-dried coating, which helps reduce premature consumption of incident light on the surface, allowing for more thorough curing of the coating near the paper base. Subsequently, the shorter wavelength ultraviolet light completes the surface curing, improving the curing adequacy of areas directly exposed to contamination, wiping, and abrasion. This process avoids problems that may arise from simply increasing the total irradiation dose of a single wavelength, such as excessively rapid surface curing with insufficient internal curing, excessive paper heating, or uneven energy utilization. It also harmonizes the adhesion, surface abrasion resistance, and ease of cleaning between the coating and the printing and decorative base paper. By coordinating the pre-drying temperature, pre-drying time, the interval between the two irradiations, and the cooling conditions, it also reduces moisture retention, surface stickiness, winding adhesion, and damage to the pattern and color, making it suitable for stable implementation under continuous roll coating production conditions.
[0019] 4. This application incorporates polymerizable UV absorbers, long-wavelength macromolecular photoinitiators, and short-wavelength macromolecular photoinitiators into the photocuring component, supplemented with nano-silica and nano-zinc oxide, to achieve a relatively complete technical balance between curing efficiency, photostability, and durability of the antifouling coating. The polymerizable UV absorbers are fixed within the coating during photocuring, reducing the likelihood of migration, precipitation, and decreased protective capacity under long-term light exposure, humidity, or wiping conditions compared to directly adding ordinary small-molecule UV absorbers. The macromolecular photoinitiators help reduce the residue of migratable small molecules after photocuring. Nano-zinc oxide and nano-silica are used as inorganic functional components in this application. Their role is not to pursue a single hardness index in isolation, but rather to work in conjunction with the aforementioned polymerizable photostability components to improve the overall retention of the coating after UV irradiation, temperature and humidity changes, and mechanical abrasion, thereby mitigating yellowing, loss of gloss, decreased adhesion, and increased pollutant retention, extending the effective service life of the decorative paper in furniture panels, wall panels, and interior finishes.
[0020] 5. This application, taking into account the characteristics of printed decorative base paper—high liquid absorbency, thin thickness, and high continuous processing speed—limits the application amount of the anti-fouling coating to 5 g / m². 2 ~20g / m 2This process employs a combination of anilox roller coating, pre-drying at 45℃–65℃, and two-stage UV curing. This process forms a complete protective layer without excessively increasing paper basis weight or surface thickness, while reducing the risks of high moisture content, unstable curing, and paper warping caused by directly applying water-based coatings to the UV curing stage. Appropriate pre-drying temperature also helps avoid color differences in printed patterns due to prolonged high-temperature processing. The coating is composed of water-dispersible components, eliminating the need for temporary addition of isocyanate curing agents during application, simplifying mixing, conveying, roller coating, and equipment cleaning; it also reduces the impact of the pot life of two-component materials on continuous production. By precisely controlling the roller coating speed, roller pressure, irradiation dose, and post-curing cooling conditions, the consistency of coating thickness and appearance across different batches can be improved. This method can be integrated with existing decorative paper printing, drying, and winding production lines, demonstrating significant value for widespread implementation and industrial application. Attached Figure Description
[0021] The present application will be described in more detail below based on embodiments and with reference to the accompanying drawings. Wherein: Figure 1 The image shows the three-dimensional distribution of the residual area ratio of four typical pollutants after cleaning in each of the embodiments, blank samples, and comparative examples in Test Example 1.
[0022] Figure 2 The graph shows the change in the residual area ratio of oil-based markers after cleaning in each embodiment, blank sample, and comparative example in Test Example 2 after different wear cycles.
[0023] Figure 3 The graph shows the detection results of formaldehyde, TVOC, free diisocyanate and propylene carbonate in each example, blank sample and comparative example in Test Example 3. Detailed Implementation
[0024] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0025] In the following examples, unless otherwise specified, all parts are parts by weight of solids, and all water used is deionized water. The cyclic carbonate equivalent of the polyfunctional cyclic carbonate and the amino active hydrogen equivalent of the polyetheramine and amino-containing hyperbranched polysiloxane were determined by titration, and the corresponding batches of raw materials were selected accordingly to ensure that the mass feed and the molar ratio of cyclic carbonate groups and amino active hydrogen simultaneously met the following set values.
[0026] In the examples and comparative examples used for performance testing, the paper was cut to the same size, and the back of the paper was bonded to the surface of the same batch of 12mm medium-density fiberboard using the same batch of water-based polyvinyl acetate adhesive; the amount of adhesive applied, the bonding pressure, and the curing time were kept consistent. For the detection of hazardous substance release and residues, no bonding substrate or adhesive was used; samples were taken directly from the prepared decorative paper to eliminate interference from the substrate and adhesive.
[0027] The epoxidized soybean oil (CAS No. 8013-07-8) and epoxidized linseed oil (CAS No. 8016-11-3) used in this application were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; polyoxypropylene diamines D-230, D-400, D-2000 and polyoxypropylene triamine T-403 were Huntsman JEFFAMINE series products, purchased from Huntsman Chemical Trading (Shanghai) Co., Ltd. or its authorized distributors, of which D-230 and D-400 were... The CAS numbers for the polyetheramines corresponding to 0 and D-2000 are 9046-10-0, and for T-403, it is 39423-51-3. 3-Aminopropyltriethoxysilane, methyltriethoxysilane, and trimethylethoxysilane are commercially available KH-550, MTES, and TMES, respectively, with CAS numbers 919-30-2, 2031-67-6, and 1825-62-3, purchased from Hubei Xinlantian New Materials Co., Ltd. The amino-containing hyperbranched polysiloxane, carbonated epoxy vegetable oil, and water-dispersible polyhydroxycarbamate were all prepared according to the method described in this application.
[0028] Polyethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate, and ethoxylated bisphenol A dimethacrylate were purchased from Changxing Special Materials (Zhuhai) Co., Ltd., with CAS numbers 26570-48-9, 28961-43-5, and 41637-38-1, respectively. Omnipol TP, Omnipol 910, Omnipol BP, and Omnipol ASA were purchased from IGM Resins' sales channels in China, and GENOPOL TX-2 and GENOPOL AB-2 were purchased from authorized distributors of the RAHN Group. The above-mentioned commercial macromolecular photoinitiators are identified by their trade names and manufacturers. 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl methacrylate and 4-methacryloyloxy-2-hydroxybenzophenone have CAS numbers 96478-09-0 and 2035-72-5, respectively. Polymerizable UV absorbers were purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd. or custom-purchased according to their chemical names. Unmodified nano-zinc oxide and different types of nano-silica were purchased from Hangzhou Jikang New Materials Co., Ltd., and 2,4,7,9-tetramethyl-5-decyn-4,7-diol (CAS number 126-86-3) was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Except for the raw materials specifically mentioned above, all other conventional reagents, decorative base paper, and water-based decorative inks are commercially available products.
[0029] Example 1
[0030] This embodiment provides a highly stain-resistant decorative paper, the preparation process of which includes the following steps S1-S4.
[0031] S1: Preparation of water-dispersible polyhydroxycarbamate.
[0032] 100 kg of commercially available epoxidized soybean oil was added to a pressure-resistant reactor, along with 0.9 kg of tetrabutylammonium bromide. After sealing, carbon dioxide was introduced until the pressure reached 3.5 MPa, and the reaction was carried out at 90°C for 11 hours. After the reaction was completed, the temperature was lowered, the pressure was released, and the mixture was filtered to obtain carbonated epoxidized soybean oil.
[0033] By weight, 50 parts of 3-aminopropyltriethoxysilane, 40 parts of methyltriethoxysilane, and 12.5 parts of trimethylethoxysilane were mixed; 60 parts of water, 50 parts of ethanol, and 12.5 parts of 1% hydrochloric acid were mixed and added dropwise to the silane mixture over 30 minutes at 35°C. After the addition was completed, the mixture was hydrolyzed and condensed at 62.5°C for 8 hours. Then, ethanol and water were removed at 45°C under a vacuum of -0.075 MPa to obtain an amino-containing hyperbranched polysiloxane.
[0034] S1.1: According to the mass ratio of carbonated epoxidized soybean oil, polyoxypropylene diamine D-230 and amino-containing hyperbranched polysiloxane of 100:18:7.5, 100 kg of carbonated epoxidized soybean oil is mixed with 85 wt% of the total amount of D-230, i.e., 15.3 kg of D-230, and reacted at 70℃ for 3.5 h.
[0035] S1.2: Add the remaining 2.7 kg D-230 and 7.5 kg amino-containing hyperbranched polysiloxane, and react at 85 °C for 1 h; according to the raw material equivalent determination results, the molar ratio of cyclic carbonate groups to amino active hydrogen is 1.085:1.
[0036] S1.3: Add 4 wt% propylene carbonate (4 kg propylene carbonate) relative to the carbonated epoxidized soybean oil, and continue the reaction at 55°C for 1.25 h; then add water until the solid content of the dispersion is 40 wt%, and disperse at 3000 r / min for 10 min to obtain a water-dispersible polyhydroxycarbamate. No isocyanate compounds are added during the above reaction process.
[0037] S2: Taking 100 kg of solid polyhydroxycarbamate in water-dispersible polyhydroxycarbamate as an example, 0.2 kg of sodium polyacrylate was dissolved in 40 kg of water, followed by the sequential addition of 2 kg of fumed hydrophilic nano-silica and 1.5 kg of unmodified nano-zinc oxide with an average primary particle size of 50 nm. The mixture was dispersed at 2000 r / min for 15 min. Subsequently, water-dispersible polyhydroxycarbamate, 15 kg of water-dispersible polyethylene glycol diacrylate, 0.5 kg of polymeric TPO-L photoinitiator Omnipol TP, 0.5 kg of a long-wavelength composite photoinitiator system composed of GENOPOL TX-2 and GENOPOL AB-2 in a mass ratio of 1:0.5, 0.75 kg of polymeric aminoalkyl phenyl ketone photoinitiator Omnipol 910, 0.75 kg of a short-wavelength composite photoinitiator system composed of Omnipol BP and Omnipol ASA in a mass ratio of 1:0.5, and 0.5 kg of... An antifouling coating was prepared by mixing 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl methacrylate and 0.225 kg of 2,4,7,9-tetramethyl-5-decyn-4,7-diol at 800 r / min for 20 min.
[0038] S3: At a quantitative concentration of 65g / m 2 Water-based decorative inks were used for gravure printing on the surface of titanium dioxide decorative base paper. The dry coating weight of the water-based decorative inks was 1.9 g / m². 2The paper is dried at 100℃ for 30 seconds to obtain the printing and decorative base paper. An anti-fouling coating is then applied to the surface of the base paper using an anilox roller at a speed of 23.5 m / min, a roller pressure of 0.60 MPa, and a coating weight of 5 g / m². 2 Then pre-dry at 55℃ for 5 minutes.
[0039] S4: Internal pre-curing is performed using ultraviolet light with a wavelength of 395nm and an irradiation intensity of 1.0W / cm². 2 The irradiation dose was 600 mJ / cm. 2 After a 1-second interval, surface curing was performed using ultraviolet light with a wavelength of 375 nm and an irradiation intensity of 2.0 W / cm². 2 The irradiation dose was 300 mJ / cm. 2 After surface curing, the paper is cooled at 27.5℃ for 5 minutes to obtain highly stain-resistant decorative paper.
[0040] Example 2
[0041] This embodiment provides a highly stain-resistant decorative paper, the preparation process of which includes the following steps S1-S4.
[0042] S1: Add 100 kg of commercially available epoxidized linseed oil to a pressure-resistant reactor, add 1.5 kg of tetrabutylammonium iodide, introduce carbon dioxide to a pressure of 1.0 MPa, react at 110°C for 16 h, cool down and depressurize, and filter to obtain carbonated epoxidized linseed oil.
[0043] By weight, 20 parts of 3-aminopropyltriethoxysilane, 55 parts of methyltriethoxysilane, and 20 parts of trimethylethoxysilane were mixed; 20 parts of water, 100 parts of ethanol, and 20 parts of hydrochloric acid with a mass concentration of 1% were mixed and added dropwise to the silane mixture over 60 minutes at 20°C; the mixture was then hydrolyzed and condensed at 75°C for 3 hours; and finally, ethanol and water were removed at 55°C under a vacuum of -0.09 MPa to obtain an amino-containing hyperbranched polysiloxane.
[0044] S1.1: According to the mass ratio of carbonated epoxy linseed oil, polyoxypropylene diamine D-400 and amino-containing hyperbranched polysiloxane of 100:31.5:12, 100 kg of carbonated epoxy linseed oil is mixed with 60 wt% of the total amount of D-400, i.e., 18.9 kg of D-400, and reacted at 82.5℃ for 5 h.
[0045] S1.2: Add the remaining 12.6 kg D-400 and 12 kg amino-containing hyperbranched polysiloxane, and react at 60 °C for 2.5 h; the molar ratio of cyclic carbonate groups to amino active hydrogen is 1.15:1.
[0046] S1.3: Add 0.5 kg of propylene carbonate and continue the reaction at 65 °C for 2 h; then add water until the solid content of the dispersion is 45 wt%, and disperse at 1000 r / min for 25 min to obtain water-dispersible polyhydroxycarbamate. No isocyanate compounds are added during the reaction.
[0047] S2: Based on 100 kg of solid polyhydroxycarbamate, add 0.5 kg of sodium polyacrylate to 15 kg of water, then add 3 kg of silica sol-type nano-silica and 0.5 kg of unmodified nano-zinc oxide with an average primary particle size of 20 nm. Disperse at 2500 r / min for 12 min. Add water-dispersible polyhydroxycarbamate, 22.5 kg of water-dispersible ethoxylated trimethylolpropane triacrylate, 1.5 kg of a long-wavelength complex photoinitiator system composed of GENOPOL TX-2 and GENOPOL AB-2 in a mass ratio of 1:1.0, 0.5 kg of a short-wavelength complex photoinitiator system composed of Omnipol BP and Omnipol ASA in a mass ratio of 1:1.0, 1.0 kg of 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, and 0.40 kg of... 2,4,7,9-Tetramethyl-5-decyn-4,7-diol was mixed at 900 r / min for 20 min to prepare an anti-fouling coating.
[0048] S3: At a quantitative concentration of 82.5 g / m 2 Water-based decorative inks for gravure printing on titanium dioxide decorative base paper have a dry coating weight of 3.0 g / m². 2 The coating was dried at 70℃ for 75 seconds. The anti-fouling coating was applied using an anilox roller in the forward direction at a speed of 35 m / min, a roller pressure of 0.20 MPa, and a coating weight of 12.5 g / m². 2 Pre-dry at 65℃ for 1 min.
[0049] S4: Internal pre-curing is performed using 400nm ultraviolet light with an irradiation intensity of 1.5W / cm². 2 The irradiation dose was 200 mJ / cm. 2 After a 10.5-second interval, surface curing was performed using ultraviolet light with a wavelength of 385 nm and an irradiation intensity of 0.8 W / cm². 2 The irradiation dose was 600 mJ / cm. 2 The paper was then cooled at 35°C for 1 minute to obtain highly stain-resistant decorative paper.
[0050] Example 3
[0051] This embodiment provides a highly stain-resistant decorative paper, the preparation process of which is as follows: steps S1-S4.
[0052] S1: Add 100 kg of commercially available epoxidized soybean oil to a pressure-resistant reactor, add 0.3 kg of tetraethylammonium bromide, introduce carbon dioxide to a pressure of 2.25 MPa, react at 130°C for 6 hours, cool down and depressurize, and filter to obtain carbonated epoxidized soybean oil.
[0053] By weight, 35 parts of 3-aminopropyltriethoxysilane, 70 parts of methyltriethoxysilane, and 5 parts of trimethylethoxysilane were mixed; 40 parts of water, 150 parts of ethanol, and 5 parts of 1% hydrochloric acid were mixed and added dropwise to the silane mixture over 90 min at 27.5 °C; the mixture was then hydrolyzed and condensed at 50 °C for 5.5 h; and finally, ethanol and water were removed at 65 °C under a vacuum of -0.06 MPa to obtain an amino-containing hyperbranched polysiloxane.
[0054] S1.1: Polyoxypropylene diamine D-2000 and polyoxypropylene triamine T-403 are mixed at a mass ratio of 3:2 to form a high molecular weight polyetheramine; according to the mass ratio of carbonated epoxidized soybean oil, high molecular weight polyetheramine and amino-containing hyperbranched polysiloxane of 100:45:3, 100 kg of carbonated epoxidized soybean oil is mixed with 72.5 wt% of the total amount of high molecular weight polyetheramine, i.e., 32.625 kg of high molecular weight polyetheramine, and the mixture is reacted at 95°C for 2 h.
[0055] S1.2: Add the remaining 12.375 kg of high molecular weight polyetheramine and 3 kg of amino-containing hyperbranched polysiloxane, and react at 72.5 °C for 4 h; the molar ratio of cyclic carbonate groups to amino active hydrogen is 1.02:1.
[0056] S1.3: Add 2.25 kg of propylene carbonate and continue the reaction at 75 °C for 0.5 h; then add water until the solid content of the dispersion is 50 wt%, and disperse at 2000 r / min for 40 min to obtain water-dispersible polyhydroxycarbamate. No isocyanate compounds are added during the reaction.
[0057] S2: Based on 100 kg of solid polyhydroxycarbamate, add 0.8 kg of sodium polyacrylate to 27.5 kg of water, then add 1 kg of γ-methacryloyloxypropyltrimethoxysilane-modified nano-silica and 1.0 kg of unmodified nano-zinc oxide with an average primary particle size of 35 nm. Disperse at 2200 r / min for 15 min. Add water-dispersible polyhydroxycarbamate, 30 kg of water-dispersible ethoxylated bisphenol A dimethacrylate, 0.5 kg of a long-wavelength complex photoinitiator system composed of GENOPOL TX-2 and GENOPOLAB-2 in a mass ratio of 1:1.5, 1.0 kg of a short-wavelength complex photoinitiator system composed of Omnipol BP and Omnipol ASA in a mass ratio of 1:1.5, 1.5 kg of 4-methacryloyloxy-2-hydroxybenzophenone, and 0.05 kg of... 2,4,7,9-Tetramethyl-5-decyn-4,7-diol was mixed at 800 r / min for 25 min to prepare an antifouling coating.
[0058] S3: At a quantitative concentration of 100g / m 2 Water-based decorative inks for gravure printing on titanium dioxide decorative base paper have a dry coating weight of 0.8 g / m². 2 Dry at 85℃ for 120 seconds; apply the anti-fouling coating using an anilox roller in the forward direction at a speed of 12 m / min, a roller pressure of 0.40 MPa, and a coating amount of 20 g / m². 2 Pre-dry at 45℃ for 3 minutes.
[0059] S4: Internal pre-curing is performed using ultraviolet light with a wavelength of 405nm and an irradiation intensity of 0.5W / cm². 2 The irradiation dose was 400 mJ / cm. 2 After a 20-second interval, surface curing was performed using ultraviolet light with a wavelength of 365 nm and an irradiation intensity of 1.4 W / cm². 2 The irradiation dose was 900 mJ / cm. 2 The paper was then cooled at 20°C for 3 minutes to obtain highly stain-resistant decorative paper.
[0060] Blank sample example The same quantitative method as in Example 2 was used, with a concentration of 82.5 g / m³. 2 The titanium dioxide decorative base paper, water-based decorative ink, and gravure printing process enable the dry coating weight of the water-based decorative ink to be 3.0 g / m². 2 The paper is dried at 70°C for 75 seconds; after printing, no anti-fouling coating is applied, and no UV curing is performed, directly producing blank printed decorative paper. Except for the detection of harmful substance release and residue, it is bonded to the surface of medium-density fiberboard according to the above-mentioned unified bonding method before testing.
[0061] Comparative Example 1 This comparative example was used to investigate the effect of amino-containing hyperbranched polysiloxanes on the crosslinking structure and stain resistance of the coating. It was based on Example 2, except that amino-containing hyperbranched polysiloxanes were not added during the preparation of the water-dispersible polyhydroxycarbamate. Specifically, 100 kg of carbonated epoxy linseed oil was reacted with 18.9 kg of D-400 at 82.5 °C for 5 h, then the remaining 12.6 kg of D-400 was added, and the reaction was carried out at 60 °C for 2.5 h; subsequently, 0.5 kg of propylene carbonate was added, and the reaction was carried out at 65 °C for 2 h. Water was added until the solid content was 45 wt%, and the mixture was dispersed at 1000 r / min for 25 min. The composition of the stain-resistant coating, the printing and decorative base paper, the coating amount, the pre-drying conditions, and the dual-band UV curing conditions were all the same as in Example 2, resulting in a comparative decorative paper without amino-containing hyperbranched polysiloxanes.
[0062] Comparative Example 2 This comparative example was used to investigate a step-by-step curing method involving pre-curing the interior with long-wavelength light followed by surface curing with short-wavelength light. The water-dispersible polyurethane, anti-fouling coating, and printing decorative base paper were all prepared according to Example 2, with the coating and pre-drying conditions being the same as in Example 2. After pre-drying, instead of two separate wavelength curing cycles, only a single curing was performed using 375nm ultraviolet light at an irradiance of 1.2 W / cm². 2 The irradiation dose was 800 mJ / cm. 2 This makes its total irradiation dose similar to 200 mJ / cm² in Example 2. 2 and 600mJ / cm 2 The sum is the same; after curing, it is cooled at 35℃ for 1 minute to obtain a single-band cured contrast decorative paper.
[0063] Comparative Example 3 This comparative example is used to compare the differences between waterborne polyurethanes produced via non-isocyanate routes and those produced via conventional isocyanate routes. By weight, 100 parts of polycaprolactone diol and 42 parts of isophorone diisocyanate were mixed under nitrogen protection, and 0.05 parts of bismuth neodecanoate were added. The mixture was reacted at 75°C for 2 hours. Then, 6 parts of 2,2-dimethylolpropionic acid and 3 parts of 1,4-butanediol were added, and the mixture was reacted at 80°C for 3 hours. After cooling to 45°C, 4.5 parts of triethylamine were added for neutralization for 20 minutes. Water was added and dispersed at 2000 rpm for 20 minutes. Finally, 0.65 parts of ethylenediamine were added for chain extension, yielding a conventional isocyanate-based waterborne polyurethane with a solid content of 45 wt%.
[0064] Taking 100 kg of polyurethane solids in the conventional waterborne polyurethane as an example, it was used to replace the water-dispersible polyhydroxycarbamate in Example 2; the remaining anti-fouling coating components and dosages, printing decorative base paper, roller coating parameters, pre-drying conditions and dual-band UV curing conditions were the same as in Example 2, and a conventional isocyanate route waterborne polyurethane comparative decorative paper was prepared.
[0065] Test Example 1: Surface resistance to contamination and ease of cleaning Five samples were randomly selected from Examples 1-3, the blank sample example, and Comparative Examples 1-3, respectively. Each sample was adhered to a medium-density fiberboard (MDF) using the same method and equilibrated for 48 hours at 23℃±2℃ and 50%±5% relative humidity. Following the surface stain resistance evaluation method of GB / T 17657-2022, 0.20 mL of soy sauce, 0.20 mL of coffee, and 0.20 mL of cooking oil were respectively added to the surface of each sample, covering an area of 100 mm². 2 Oily marker pen marks were removed and left to stand for 24 hours. The marks were then rubbed for 20 cycles under a 500g load using a nonwoven fabric containing 5wt% neutral detergent, wiped with water, and dried before evaluation.
[0066] The color difference ΔE of the contaminated area before and after cleaning was measured using a D65 light source and a 10° observer condition. 00 Simultaneously, images were acquired under fixed lighting, shooting distance, and exposure parameters. The cleaned images were converted to the Lab color space, and the residual contamination areas were binarized and segmented using the mean color difference of the uncontaminated areas plus three times the standard deviation as the segmentation threshold. The residual contamination area ratio R was calculated according to R=A. r Calculate A0×100%, where A r A0 represents the area of pixels identified as having residual contamination after cleaning, and A0 is the initial contamination coverage area. The results are the average of five parallel samples, as shown in Table 1 and... Figure 1 It should be noted that, Figure 1 The continuous surfaces in the model are only used to connect discrete test points and enhance 3D readability; statistical calculations use the original discrete data.
[0067] Table 1. Stain resistance and easy cleaning performance of each sample
[0068] From Table 1 and Figure 1As can be seen, Examples 1-3 all formed three-dimensional residual ridges with low positions and small undulations under all four types of pollutants, and the average residual area ratio of pollutants was reduced by about 89% to 94% compared with the blank sample. The average color difference after cleaning was controlled at 1.1 to 1.8. Example 2 had the lowest residual amount of all four types of pollutants, indicating that the combination of intermediate coating amount and sufficient dual-band curing can form a more continuous cross-linked layer on the pattern surface. The average residual amount of comparative examples 1 and 2 was about 4.4 times and 3.1 times that of example 2, respectively, and the increase in oily marker pen residue was more obvious. This indicates that the low surface energy branching nodes formed by amino-containing hyperbranched polysiloxane and the deep-surface gradient network formed by long-wave and short-wave curing are not simply parallel, but jointly restrict the entry of oily pollutants into the coating. The dispersion of each parallel result was low, and there was no accidental improvement dependent on a single pollutant, which indirectly supports the stable stain resistance and easy cleaning advantages of this application against a variety of common indoor pollutants.
[0069] Test Example 2: Stain Retention Performance After Abrasion and Light Aging Each group of bonded samples was subjected to abrasion using a CS-10F grinding wheel at a load of 500g and a rotation speed of 60r / min. The residual area percentage of oil-based marker stains after standardized wiping was measured after 0, 250, 500, and 1000 cycles. Separate samples from the same group were subjected to accelerated aging under a xenon lamp with an irradiation intensity of 0.35W / m². 2 At 340nm, with a blackboard temperature of 63℃±3℃, a cycle of 102min light exposure and 18min spray was used. After aging for 168h, color difference, adhesion, and residual area rate of oil-based marker stains were measured. Abrasion weight loss was calculated as the mass difference of the sample before and after 1000 abrasion cycles; stain resistance retention was calculated as (100-R1) / (100-R0)×100%, where R0 is the residual area rate of stains before aging, and R1 is the residual area rate of stains after aging. Five parallel samples were set up for each group.
[0070] Table 2. Test results of wear resistance and post-aging performance of each sample.
[0071] From Table 2 and Figure 2It can be seen that with the increase of abrasion cycles, the residual area ratio of each sample showed an upward trend, but the slope of the curves of Examples 1-3 was significantly smaller than that of the blank sample and the three comparative examples. After 1000 abrasion cycles, the example group still maintained a low marker pen residue, with the increase in Example 2 being only 4.2 percentage points. Comparative Example 1 showed significantly faster abrasion weight loss and residue growth after the absence of hyperbranched polysiloxane, indicating that branched siloxane not only improved the initial surface condition but also improved the coating integrity through multi-point embedding of polyhydroxyurethane network. Although the total irradiation dose of Comparative Example 2 was the same as that of Example 2, its residue and photo-aged color difference were higher, indicating that the curing effect cannot be explained by the total energy alone. The sequence of first using long-wavelength light to promote network formation inside the coating and then using short-wavelength light to improve the degree of surface transformation has an independent technical contribution. The stain resistance retention rate of the example group after aging all exceeded 96%, reflecting that the polymerizable UV absorber, after being fixed in the cross-linked network, can reduce migration loss and, together with the inorganic functional components, delay the surface defects caused by photoaging.
[0072] Test Example 3: Detection of Hazardous Substance Release and Characteristic Residues The prepared decorative paper was placed at 23℃±2℃ and 50%±5% relative humidity for 7 days without using the substrate or adhesive, and samples were directly cut for testing. Formaldehyde and TVOC emissions were tested using the environmental chamber method specified in GB 18585-2023 "Limits of Hazardous Substances in Wallpaper for Interior Decoration and Renovation Materials," at a 1m³ temperature. 3 Environmental chamber, temperature 23℃±1℃, relative humidity 50%±5%, material load capacity 1.0m. 2 / m 3 and a ventilation rate of 0.5h -1 The mixture was equilibrated for 24 hours under the specified conditions; formaldehyde was determined by DNPH derivatization-HPLC method, and TVOC was determined by Tenax tube sampling-thermal desorption-GC-MS method.
[0073] For the detection of free diisocyanates, 1.00 g of shredded sample was placed in 10 mL of anhydrous acetonitrile containing dibutylamine derivatizing agent, ultrasonically extracted for 30 min, and allowed to stand for derivatization for 60 min. TDI, MDI, HDI, and IPDI were determined by HPLC-MS / MS, and the total amount of these four components was taken as the total free diisocyanate. The method limit of quantitation was 0.05 mg / kg. Residual propylene carbonate was determined by headspace GC-MS. The headspace equilibration temperature was 80 °C, and the equilibration time was 30 min. The method limit of quantitation was 0.50 mg / kg. Each group was analyzed in triplicate.
[0074] Table 3. Hazardous substance release and characteristic residues of each sample
[0075] It should be noted that, Figure 3(c) The inverted triangle indicates values below the corresponding quantitative values; Figure 3 The scatter plots represent parallel measurements, and the large dots represent the average value. Figure 3 In this context, "Example 1" is an abbreviation for "Example 1", and "Comparative Example 2" is an abbreviation for "Comparative Example 2". Figure 3 The abbreviation rules for other horizontal coordinates in each coordinate system are the same and will not be repeated here; "blank" refers to the corresponding test results of the decorative paper prepared from the blank sample.
[0076] From Table 3 and Figure 3 As can be seen, the formaldehyde and TVOC emissions in Examples 1-3 were all at low levels and significantly lower than the reference limits shown in the figure. No TDI, MDI, HDI, or IPDI were detected in the three examples using the non-isocyanate ring-opening addition route, the blank sample example, and Comparative Examples 1-2. However, free diisocyanate was detected in Comparative Example 3, which used the conventional isocyanate route. This result indicates that not adding isocyanate compounds does not merely change the synthetic name, but eliminates the main source of free diisocyanate monomer residue from the raw material pathway. The residual propylene carbonate in the examples was at a low level, with Example 3 showing the lowest level due to the higher temperature in the later stages. Simultaneously, its TVOC did not increase significantly due to the multi-component photocuring system, indicating that the macromolecular photoinitiator system and polymerizable UV absorber are beneficial in reducing small molecule migration and volatilization. The above tests only prove that the listed releases or residues are below the corresponding limits or method limits of quantitation, and should not be construed as the product being absolutely harmless to humans. However, they support the claim that this application has a low risk of harmful substance release and characteristic residues when applied to indoor decoration scenarios.
[0077] While the invention has been described with reference to preferred embodiments, various modifications can be made thereto, and components or technical features can be replaced with equivalents without departing from the scope of the invention. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no conflict in structural or technical concept. The invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing highly stain-resistant decorative paper, characterized in that, Includes the following steps: S1: A water-dispersible polyhydroxycarbamate is prepared by ring-opening addition of a multifunctional cyclic carbonate, a high molecular weight polyetheramine and an amino-containing hyperbranched polysiloxane and then water-dispersed. No isocyanate compound is added during the reaction. S2: Mix the water-dispersible polyhydroxycarbamate with a multi-band photocurable component, a polymerizable light-stabilizing component and an inorganic functional component to prepare an anti-fouling coating; S3: Roll-coat the anti-fouling coating onto the surface of the printed decorative base paper, with a coating amount of 5g / m². 2 ~20g / m 2 Pre-dry at 45℃~65℃ for 1min~5min; S4: Internal pre-curing is performed using 395nm~405nm ultraviolet light, followed by surface curing using 365nm~385nm ultraviolet light to obtain highly stain-resistant decorative paper.
2. The method for preparing highly stain-resistant decorative paper according to claim 1, characterized in that, In step S2, based on 100 parts by weight of the polyhydroxycarbamate solid in the water-dispersible polyhydroxycarbamate, the antifouling coating comprises 100 parts of water-dispersible polyhydroxycarbamate, 15-30 parts of water-dispersible multifunctional UV crosslinking agent, 0.5-1.5 parts of long-wavelength macromolecular photoinitiator, 0.5-1.5 parts of short-wavelength macromolecular photoinitiator, 0.5-1.5 parts of polymerizable UV absorber, 1-3 parts of nano-silica, 0.5-1.5 parts of nano-zinc oxide, 0.2-0.8 parts of sodium polyacrylate, 0.05-0.40 parts of 2,4,7,9-tetramethyl-5-decyn-4,7-diol, and 15-40 parts of water.
3. The method for preparing highly stain-resistant decorative paper according to claim 1, characterized in that, In step S1, the water-dispersible polyhydroxycarbamate is prepared according to the following steps: S1.1: The polyfunctional cyclic carbonate, the high molecular weight polyetheramine, and the amino-containing hyperbranched polysiloxane are mixed in a mass ratio of 100:18 to 45:3 to 12. The mixture is then reacted at 70°C to 95°C for 2 to 5 hours. S1.2: Add the remaining high molecular weight polyetheramine and amino-containing hyperbranched polysiloxane, and react at 60℃~85℃ for 1h~4h, wherein the molar ratio of cyclic carbonate groups to amino active hydrogen is 1.02:1~1.15:1; S1.3: Add 0.5wt% to 4wt% of propylene carbonate relative to the polyfunctional cyclic carbonate, react at 55℃ to 75℃ for 0.5h to 2h, then add water and disperse at 1000r / min to 3000r / min for 10min to 40min to obtain the water-dispersible polyhydroxycarbamate.
4. The method for preparing highly stain-resistant decorative paper according to claim 3, characterized in that, The multifunctional cyclic carbonate is carbonated epoxidized soybean oil or carbonated epoxidized linseed oil, and is prepared according to the following steps: commercially available epoxidized soybean oil or commercially available epoxidized linseed oil is placed in a reaction vessel, and 0.3wt% to 1.5wt% of a quaternary ammonium salt catalyst relative to its mass is added. Carbon dioxide is introduced to a pressure of 1.0MPa to 3.5MPa, and the reaction is carried out at 90℃ to 130℃ for 6h to 16h. The quaternary ammonium salt catalyst is one or more of tetrabutylammonium bromide, tetrabutylammonium iodide, or tetraethylammonium bromide.
5. The method for preparing highly stain-resistant decorative paper according to claim 3, characterized in that, The amino-containing hyperbranched polysiloxane is prepared according to the following steps: 20-50 parts by weight of 3-aminopropyltriethoxysilane, 40-70 parts by weight of methyltriethoxysilane, and 5-20 parts by weight of trimethylethoxysilane are mixed; 20-60 parts by weight of water, 50-150 parts by weight of ethanol, and 5-20 parts by weight of 1% hydrochloric acid are mixed and added dropwise to the silane mixture at 20℃-35℃ for 30-90 minutes; after the addition is completed, a hydrolysis-condensation reaction is carried out at 50℃-75℃ for 3-8 hours, and ethanol and water are removed under conditions of 45℃-65℃ and a vacuum of -0.06MPa--0.09MPa to obtain the amino-containing hyperbranched polysiloxane.
6. The method for preparing highly stain-resistant decorative paper according to claim 2, characterized in that, The high-molecular-weight polyetheramine is one or more of polyoxypropylene diamine D-230, polyoxypropylene diamine D-400, polyoxypropylene diamine D-2000, or polyoxypropylene triamine T-403; the water-dispersible multifunctional UV crosslinking agent is one or more of polyethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate, or ethoxylated bisphenol A dimethacrylate; the nano silica is one or more of fumed hydrophilic nano silica, silica sol nano silica, or γ-methacryloyloxypropyltrimethoxysilane modified nano silica; the nano zinc oxide is unmodified by organic surface treatment and has an average primary particle size of 20 nm to 50 nm.
7. The method for preparing highly stain-resistant decorative paper according to claim 2, characterized in that, The long-wavelength macromolecular photoinitiator is the polymeric TPO-L photoinitiator Omnipol TP, or is composed of the polymeric thioxanthone photoinitiator GENOPOL TX-2 and the polymeric amine synergist GENOPOL AB-2 in a mass ratio of 1:0.5 to 1.5; the short-wavelength macromolecular photoinitiator is the polymeric aminoalkyl benzophenone photoinitiator Omnipol 910, or is composed of the bifunctional benzophenone photoinitiator Omnipol BP and the polymeric amine synergist Omnipol ASA in a mass ratio of 1:0.5 to 1.
5.
8. The method for preparing highly stain-resistant decorative paper according to claim 2, characterized in that, The polymerizable UV absorber is one or more of 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl methacrylate, 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone or 4-methacryloyloxy-2-hydroxybenzophenone.
9. The method for preparing highly stain-resistant decorative paper according to claim 1, characterized in that, In step S3, the printed decorative base paper is processed with a basis weight of 65 g / m³. 2 ~100g / m 2 The water-based decorative ink is obtained by gravure printing on the surface of titanium dioxide decorative base paper and drying it. The dry coating weight of the water-based decorative ink is 0.8 g / m². 2 ~3.0g / m 2 The drying temperature is 70℃~100℃, and the drying time is 30s~120s; the anti-fouling coating is applied by an anilox roller in the forward direction, with a roller speed of 12m / min~35m / min and an inter-roller pressure of 0.20MPa~0.60MPa.
10. The method for preparing highly stain-resistant decorative paper according to claim 1, characterized in that, In step S4, when internal pre-curing is performed using 395nm–405nm ultraviolet light, the irradiation intensity is 0.5W / cm². 2 ~1.5W / cm 2 The irradiation dose was 200 mJ / cm. 2 ~600mJ / cm 2 After internal pre-curing, a 1-20 second interval is maintained before surface curing using 365nm-385nm ultraviolet light at an irradiation intensity of 0.8W / cm². 2 ~2.0W / cm 2 The irradiation dose was 300 mJ / cm. 2 ~900mJ / cm 2 After surface curing, cool at 20℃~35℃ for 1min~5min.
Citation Information
Patent Citations
Dirt-resistant water-based UV (ultraviolet) coating as well as preparation method and application thereof
CN115109510A